2002
DOI: 10.1001/jama.287.14.1832
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Cancer Survivors' Knowledge About Their Past Diagnosis and Treatment

Abstract: Important knowledge deficits exist among adult survivors of childhood cancer regarding basic aspects of their diagnosis and treatment. Such deficits could impair survivors' ability to seek and receive appropriate long-term follow-up care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
250
0
4

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 337 publications
(262 citation statements)
references
References 16 publications
8
250
0
4
Order By: Relevance
“…However, a recent study suggested that only 72% of survivors could accurately report their diagnosis with precision, and even fewer could accurately report on their cancer-associated therapies. 44 Survivors need the means to provide clinicians with accurate information concerning their cancer diagnosis and treatment. It is incumbent on the physicians providing care for pediatric cancer patients to provide them with an accurate summary of their treatment history, and information concerning the potential late effects of those therapies.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study suggested that only 72% of survivors could accurately report their diagnosis with precision, and even fewer could accurately report on their cancer-associated therapies. 44 Survivors need the means to provide clinicians with accurate information concerning their cancer diagnosis and treatment. It is incumbent on the physicians providing care for pediatric cancer patients to provide them with an accurate summary of their treatment history, and information concerning the potential late effects of those therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The risk for obesity was greatest among females diagnosed before 4 years of age and treated with radiation doses Ն 20 Gy (RR ϭ 3.81; 95% CI, 2.34 -5.99; P Յ 0.001). Obesity was not associated with treatment consisting of chemotherapy only or with cranial radiation doses of [10][11][12][13][14][15][16][17][18][19] Gy.…”
Section: Obesity In Survivors Of Childhood Acute Lymphoblastic Leukemiamentioning
confidence: 92%
“…To evaluate the level of knowledge of past diagnosis and treatment, a 5% sample (n ϭ 635) of CCSS participants was selected and interviewed. 12 The information obtained from survivors was compared with the information abstracted from their medical records. Overall, 72% named their diagnosis with precision, and 19% were accurate but not precise.…”
Section: Knowledge Of Cancer Diagnosis and Treatmentmentioning
confidence: 99%
“…11,12 Because many cancer treatmentrelated sequelae may not become clinically apparent until the survivor attains maturity or with the aging process, education of survivors and the health care providers supervising their care represents an important component of the transition process. Educational efforts should begin early in the continuum of cancer care and respond to the information needs of children and adolescents/young adults across the cancer survivorship spectrum from diagnosis to long-term follow-up.…”
Section: Health Educationmentioning
confidence: 99%